Ivanovo detstvo . Ivan's Childhood - Tarkovsky, Andrei (Mosfilm, 1962)
A teenager, who lost his family during the WWII, has joined the Red Army. As he collects information about the location and movements of enemy detachments, he has to live the life of a grown-up soldier and to cope with the stress and pains of war. Only in his dreams does the memory of another world - without the war - return to him. The first full feature film of Andrei Tarkovskii. Rreceived numerous prizes at film festivals in Venice, San-Francisco, Montreal, Karlovy Vary.